DOMINO THEORY FOR THE PROMULGATION OF INSTABILITY IN THE SAHEL REGION: POST GADHAFI ERA IN PERSPECTIVE - Idahosa, Stephen; Chukwujekwu , Ejike (Revista Inclusiones, 2019)
The paper models post M. Gadhafi spread of instability in the Sahel region through the lens of “domino theory”. It offers a useful scale for analysing socio-cultural and environmental dynamics that transcend national boundaries, such as spread of insurgency and instability across national frontiers. It examines effect of the fall of Gaddafi regime and its consequential spread of instability, particularly it effects in the Sahel region, evident in Mali, Niger and Nigeria. Methodologically, it employs the use of descriptive analysis relying solely on secondary information for data generation and analysis. It concludes that as long as level of insecurity and instability is high, any project towards development will be hampered.